Tratados internacionais concessivos de isenção tributária heterônoma, conforme artigo 98 do Código Tributário Nacional. - Sampaio, Marynna Mader Gouveia Cysneiros (2020)
Starting from the use of deductive-hypothetical methodology, based on international law and tax law, deepens the study on the possibility of granting exemption heteronomous by the Union, international treaties, without interfering with the jurisdiction of federal entities, leading into account the benefits of exclusion of the tax credit in the globalized world. The issue of the theme is revolves around the differences of doctrine and court decisions on the constitutionality of Article 98 of the National Tax Code, which is at variance with the precepts Article 151, III of the Federal Constitution, which expressly prohibits the introduction of tax exemptions, when powers of other federal entities. To resolve disagreements on the subject, it is necessary to take the time of the Constitution of 1969, Act 5172 of 1966 and the current highest law. But also the distinction between autonomy and sovereignty, international and national standards as well as the inclusion of treaties in the domestic legal system. And finally, it is of vast importance to stick to the purpose of tax exemptions, which result in economic, social and technological. Just as its purpose is to increase the convergence of international relations, the formation of new economic blocs, the financial stimulus as attractive for multinationals coming, the increase in scientific projects, the coming of international festivals, as well as, increasing international cultural exhibitions for the development of Brazil.